Pollutants at Lake Buyan (Bali, Indonesia) and Solutions for Improving Its Environmental State - Ni Made Savita Rasjman Rasjman; I Nyoman Adi Khrisna Wijaya; I Made Ary Putra Nata; Ni Putu Ratna Dewi Damayanti; I Wayan Budiasa; I Ketut Suada (International Journal of Biosciences and Biotechnology, 2023)
Lake Buyan in Buleleng, Bali, has various purposes, such as supplying water for crop and livestock farming and the domestic sector. Wastes generated by human activities in its immediate surroundings are increasing population pressures on the lake’s environment. According to Gubernatorial Regulation Number 16 of 2016, the lake’s water quality is in a poor state and is categorized as ‘polluted’. One of the ways proposed in this research to reduce the pollution level was to build a constructed wetland, which is a waste treatment system combining aquatic plants, soil or other growing media, and microbial assemblages. Results showed that 50 sets of vertical flow constructed wetlands with a single capacity of 40 m3 are needed around Lake Buyan. Another applicable design is concentrating wastewater flows through pipes into a 2000 m3 constructed wetland